A Comprehensive Study of Adaptive Recommendation Technologies in Education for Enhancing Personalized Learning - Thakkar, Ankita (Digital Repository of Theses - SSBM Geneva, 2025)
The traditional one-size-fits-all education model often fails to cater to the ever-evolving learning needs of students. Personalized learning supported by adaptive recommendation systems serves as a great approach to enhance the engagement and learning outcomes of students. This study examines the implementation of recommendation systems in academics. The main focus is to deliver customized and adaptive learning experiences. The research integrates machine learning techniques and advanced algorithms to analyze student performance data and recommend tailored learning paths. A comparative study of various methodologies highlights the effectiveness of adaptive systems in improving learning outcomes, student engagement and knowledge retention. Findings indicate that such systems considerably improve the learning experience of students by providing individualized support. However, challenges such as scalability, cultural adaptability, and data dependency remain critical barriers to widespread adoption. To address the above-mentioned challenges, the study explores ways for developing a robust data infrastructure, refining recommendation algorithms for varied educational contexts, and ensuring scalability across academic institutions. Additionally, the research investigates the role of emerging technologies such as AI-drives tutoring systems, in advancing personalization. The study concludes that adaptive recommendation systems hold great potential in transforming education. However, further advancements are necessary to optimize these systems for broader accessibility and effectiveness.